2019
DOI: 10.1097/hjh.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of electronic and tobacco cigarettes on vascular and respiratory function in healthy volunteers

Abstract: Our results demonstrate that acute exposure to tobacco smoking as well as electronic cigarettes influences vascular and respiratory function. Where tobacco smoking significantly increased microparticle formation, indicative of possible endothelial injury, electronic cigarettes use induced vasoreactivity and decreased peak expiratory flow. These findings suggest that both electronic cigarettes and tobacco smoking negatively impact vascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 41 publications
1
61
0
Order By: Relevance
“…2, where the vertical dashed line represents no effect and plots to the right of the vertical dashed line indicate that the TC effect is greater than the EC effect. The results of most studies [5,15,26,44,52], but not of all studies [16,25,47], are consistent with the concept that the effects of TC smoking on acute cardiovascular autonomic functions are greater than those of EC vaping. The overall mean differences between TC smoking and EC vaping across all studies was 1.58 mmHg (95% confidence interval [CI] 0.20-2.97; p = 0.025) for SBP, 1.57 mmHg (95% CI 0.37-2.78; p = 0.01) for DBP and 3.06 bpm (95% CI 2.01-4.10; p = 0.00001) for HR.…”
Section: Acute Autonomic Cardiovascular Effects Of Tc Smoking Versus supporting
confidence: 56%
See 3 more Smart Citations
“…2, where the vertical dashed line represents no effect and plots to the right of the vertical dashed line indicate that the TC effect is greater than the EC effect. The results of most studies [5,15,26,44,52], but not of all studies [16,25,47], are consistent with the concept that the effects of TC smoking on acute cardiovascular autonomic functions are greater than those of EC vaping. The overall mean differences between TC smoking and EC vaping across all studies was 1.58 mmHg (95% confidence interval [CI] 0.20-2.97; p = 0.025) for SBP, 1.57 mmHg (95% CI 0.37-2.78; p = 0.01) for DBP and 3.06 bpm (95% CI 2.01-4.10; p = 0.00001) for HR.…”
Section: Acute Autonomic Cardiovascular Effects Of Tc Smoking Versus supporting
confidence: 56%
“…Further, the sympathoexcitatory effects of acute EC use are largely attributable to nicotine-and not to the non-nicotine constituents in EC emissions [2,8,16,34]. Additionally, these sympathoexcitatory effects of acute EC vaping are less than those of acute TC smoking, as estimated by HR and BP [5,15,16,25,26,44,47,52]. Finally, limited data suggest that chronic EC use is associated with sympathetic activation [35], even in the absence of acute nicotine inhalation, although more data are needed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study we investigate whether e-cigarette use may cause similar vascular effects as demonstrated following cigarette smoking, as we and other groups have previously demonstrated [19,20]. Moreover, we investigate if nicotine is the main component for the adverse vascular effects.…”
Section: Introductionmentioning
confidence: 79%